1992
DOI: 10.1103/physrevlett.69.1911
|View full text |Cite
|
Sign up to set email alerts
|

Electron-positron pair production in Coulomb collisions of ultrarelativistic sulfur ions with fixed targets

Abstract: Angular and momentum distributions have been measured for positrons from electron-positron pairs created in peripheral collisions of 6.4-TeV sulfur ions with fixed targets of Al, Pd, and Au. The data are compared with results of several theoretical treatments. Measured differential cross sections peak at low momentum (< 1 MeV/c), extend significantly to much higher momenta (> 17 MeV/c), and concentrate sharply in the forward direction, along the ion-beam axis. Positron yields scale as the square of the target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 14 publications
4
43
0
Order By: Relevance
“…[32] shows satisfactory agreement of the positron spectra up to --8 MeV/c with the calculations of Ref. [14], but an experimental deficit above this momentum.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…[32] shows satisfactory agreement of the positron spectra up to --8 MeV/c with the calculations of Ref. [14], but an experimental deficit above this momentum.…”
Section: Resultssupporting
confidence: 73%
“…[32] is prevented by our measurement errors which tend to fiatten the spectra, and also our poor statistics.…”
Section: Resultsmentioning
confidence: 99%
“…A study of e + e − production in sulfur-induced fixed-target heavy-ion collisions at √ s NN = 20 GeV found that the positrons had a higher average energy than the electrons [254]. This difference may be explained by Coulomb corrections [255] since electrons are attracted to nuclei while positrons are repelled.…”
Section: E + E − Productionmentioning
confidence: 93%
“…Although the bound-free pair production cross section is smaller than the total lepton-pair cross section, it has a number of important implications for the LHC. Pair production has been studied at RHIC [121] and the Fermilab Tevatron [252], in addition to fixed-target experiments [253][254][255].…”
Section: Pure Qed Processesmentioning
confidence: 99%
“…In view of the experimental result of [38,39,40] which observed an almost exact Z 2 scaling of the positron yield (or, equivalently, the number of produced pairs) apparently incompatible with large Coulomb corrections, one should mention a possible shortcoming of such a model. As explained in reference [12], the Coulomb corrections in the integral Eq.…”
Section: Papers [4 11]mentioning
confidence: 99%